RESULTADOS DO PROJETO DE PESQUISA EM MECATRÔNICA NA UNIJUÍ OBTIDOS EM 2007 - VALDIERO, ANTONIO C.; LOCATELI, CRISTIANO C.; MIOTTO, FABIANE E. M.; ZAGO, FERNANDO; GILAPA, GENARO M. M.; YANSHENG, JIANG; BARBIERI, JOÃO R. P.; ENDLER, LUCIANO; RAFIKOV, MARAT; ANDRIGHETTO, PEDRO L.; DILDA, VANESSA (Salão do Conhecimento, 2013)
Resumo